Vlijanie technologii primenenija sredstv zakalivanija i dychatel'nych upražnenij na funkcional'nye pokazateli plovcov podrostkovogo vozrasta - Volkova, A. M.; Shalabodina, V. A. (Vestnik Moskovskogo gorodskogo pedagogiceskogo universiteta. Serija «Estestvennye nauki», 2020)
This article discusses the problem of the stability of the human body to adverse environmental conditions. It also determines the patterns of improving the vital functions of the human body when acquiring tolerance to systemic thermal changes in the external environment. The experimental group demonstrates the results of applying the hardening technology developed by the authors.